The Prognostic Value of Early Repolarization with ST‐Segment Elevation by Age and Gender in the Hispanic Population. Issue 12 (6th September 2015) - SHULMAN, ERIC; AAGAARD, PHILIP; KARGOLI, FARAJ; HOCH, ETHAN; BIASE, LUIGI DI; FISHER, JOHN; GROSS, JAY; KIM, SOO; PALMA, EUGEN; FERRICK, KEVIN J.; KRUMERMAN, ANDREW
Abstract : Background: Early repolarization (ER), once thought to be a benign finding on electrocardiograph (ECG), has recently been associated with an increased risk of sudden cardiac death. As there are limited data in the Hispanic population, we investigated possible associations between automated ECG ER readings and overall mortality, using the classic definition involving J‐point elevation with ST segment elevation. Methods: An ECG and electronic medical record (EMR) database from a regional medical center was interrogated. Inclusion criteria included Hispanic ethnicity and age over 18 from 2000 to 2011. A Cox model assessed the outcome of death. Varying morphological characteristics of ER were analyzed for high‐risk features. Results: There were n = 33, 944 Hispanics of who n = 532 (1.6%) had ER with a mean follow‐up period of 5.29 years. After adjustment for demographic, clinical, lifestyle, and laboratory variables, ER was not significantly related to all‐cause mortality (hazard ratio [HR]: 1.18, 95% confidence interval [CI]: 0.90–1.54, P = 0.23). However, mortality risk of ER varied by gender and age (P interaction = 0.007). The risk of ER for mortality was highest for females (HR: 2.01, CI: 1.39–3.10, P = 0.001), with the highest overall risk for women over the age of 75 (HR: 2.09, CI: 1.12–3.92, P = 0.021) compared to women under age 75 (HR: 1.72, CI: 0.95–3.11, P = 0.075). Conclusions: ER is not associated with an increased risk of death in the overall Hispanic population. However, our analysis suggests a higher risk of overall mortality in the elderly Hispanic female population with ER.